Impacts of Chlorine 1-3 ion channels on localized bladder neoplasms - Muslum, Ozer; Ahmet, Karakeci; Ebru, Onalan; Ahmet, Tektemur; Tunc, Ozan; Ahmet, Keles; Irfan, Orhan (Cellular and Molecular Biology Association, 2024)
Bladder tumors occur more frequently in men than in women and are the fourth most common malignancy after prostate, lung, and colon cancers. In this study, we examined the expression of chlorine ion channel 1 and chlorine ion channel 3 in localized bladder tumors according to their stage. We conducted a retrospective analysis of a prospective cohort study spanning from May 2018 to January 2020. This study involved a group of 55 patients who had been diagnosed with primary bladder cancer and underwent transurethral resection of bladder tumor under either general or spinal anesthesia. In addition, 30 patients who underwent cystoscopy due to etiology of hematuria and biopsies were taken from suspicious areas and whose results were normal were included as the control group. The collected samples were evaluated using real-time polymerase chain reaction in a medical genetics laboratory. In our study, it was observed that chlorine ion channel 3 gene expression increased significantly (P<0.001) in all cancer tissues compared to the control group, whereas no significant increase was found in chlorine ion channel 1 gene expression compared to the control group. The data obtained, especially for chlorine ion channel 3, are promising in terms of their use in the treatment of bladder tumors in humans. © 2024 Cellular and Molecular Biology Association. All rights reserved.
Keywords: Bladder; Chlorine; ClC-3; Ion channel; Tumor